2004
DOI: 10.1143/jjap.43.l1072
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Piezoelectric Properties of ZnO-added (Na0.5K0.5)NbO3 Ceramics

Abstract: The orthorhombic structure of (Na0.5K0.5)NbO3 (NKN) ceramics was maintained when ZnO was added. NKN ceramics have a porous microstructure and dissolve when they are exposed to water. However, as ZnO was added, a dense microstructure was developed and deliquescence was not observed. The mechanical quality factor (Q m) and coercive field (E c) increased with the addition of ZnO, indicating that ZnO acted as a hardener in the NKN ceramics. The dielectric constant (ε … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(104 citation statements)
references
References 10 publications
6
97
1
Order By: Relevance
“…Meanwhile, with the increase of inhomogeneity, the best sintering conditions such as BaTiO 3 content and sintering temperature show the deviation with the conditions of normal sintering. 24 …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, with the increase of inhomogeneity, the best sintering conditions such as BaTiO 3 content and sintering temperature show the deviation with the conditions of normal sintering. 24 …”
Section: Introductionmentioning
confidence: 99%
“…We propose that the broadened peaks at higher values of T s in the MWS-derived ceramics may be ascribed to the improvement in density and/or grain size, which contributes to decrease the leakage current and enhances the ferroelectricity. It was also reported that the increased sintering temperature in (Na 0.5 K 0.5 )NbO 3 -based materials can enhance ferroelectricity [39] or rhombohedral symmetry in MWS-derived specimens [16,[23][24][25][26][27][28][29][30][31]. Previous studies on the effect of BaZrO 3 (BZ)-modification on the crystal structure of BNKT ceramics [32] have found that the BZ modification induces a phase transition from rhombohedral to pseudocubic symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers used hot pressing or spark plasma sintering (SPS) techniques to yield better quality ceramics. 5) Recently, an efficient solution to improve these problems has been realized by using some additives in NKN ceramics, such as ZnO, 6) 14) A comparison of the properties of (Na 0.5 K 0.5 )NbO 3 ceramics based on the previous reports of various groups is shown in Table 1. Thus, the addition of some perovskite compounds to form solid solutions with NKN or synthesizing by Spark Plasma Sintering (SPS) has been made to obtain lead-free materials suitable for industrial applications.…”
Section: Introductionmentioning
confidence: 99%